Enviromental Credits Accounting dan Peran Akuntansi Dalam Transisi Hijau: Kajian Literatur - Simatupang, Erik Martua; Dani, Muhammad Riyan; Anakampun, Arif; Darma, Jufri (Universitas Pahlawan Tuanku Tambusai, 2025)
The global environmental crisis, marked by climate change, rising carbon emissions, and the degradation of natural resources, has created an urgent demand for transparent and accountable reporting systems. International regulatory pressures, such as the Paris Agreement and carbon pricing policies, have compelled companies to shift their focus not only toward profitability but also toward long-term sustainability. In this context, accounting plays a strategic role in providing relevant information on sustainability activities, particularly through the application of environmental credits accounting, which involves the recognition, measurement, and reporting of carbon credits and other environmental instruments. This article aims to examine the role of accounting in supporting the green transition by reviewing literature on the concepts, practices, and challenges of implementing environmental credits accounting. The research method employed is a literature review by analyzing recent scholarly sources, institutional reports, and sustainable accounting standards. The findings indicate that environmental credits accounting significantly contributes to enhancing transparency in sustainability reporting, supporting green investment decisions, and strengthening corporate legitimacy in response to increasingly stringent environmental regulations. Nevertheless, key challenges remain, including inconsistencies in reporting standards, limitations in valuation methods, and the lack of harmonized cross-country policies. In conclusion, accounting plays a central role in accelerating the green transition; however, consistent regulatory frameworks and standardized reporting practices are essential to ensure its effective implementation.